Sleep and Psychological Difficulties in Italian School-Age Children During COVID-19 Lockdown. (31st January 2021) - Cellini, Nicola; Di Giorgio, Elisa; Mioni, Giovanna; Di Riso, Daniela
Abstract: Objective: On March 10, 2020, the Italian Government ordered a national lockdown to limit the viral transmission of coronavirus disease 2019 infections. This study investigated how these restrictive measures have impacted sleep quality, timing, and psychological difficulties in school-age children and their mothers during the lockdown. Methods: In an online survey, 299 mothers reported their sleep habits, experience of time, and psychological difficulties as well as those of their children (6–10 years old) during and, retrospectively, before the lockdown. Results: During the lockdown, children showed a marked delay in sleep timing—that is, later bedtime and rise time—and a mild worsening in sleep quality. They were less prone to respect daily routines or to keep track of the passage of time. They showed increased emotional, conduct, and hyperactive symptoms, and the increase in these psychological difficulties was predicted by the change in sleep quality, boredom, and mothers' psychological difficulties. In addition, mothers showed a delayed sleep timing and worsening of sleep quality during the lockdown, in varying degrees depending on their working conditions. Mothers who kept working regularly outside their homes during lockdown reported more regular sleep patterns, whereas mothers who stopped working showed more emotional symptoms and relevant changes in their perception of time. Conclusions: Overall, given the evidence of the adverse behavioral and psychological impact of home confinement and social restrictions, effective measures needed to be in place to mitigate long-term effects on children and their mothers, especially those who have had to stop working during lockdown.